Trend and cycle features in German residential investment before and after reunification - Thomas A. Knetsch (Deutsche Bundesbank, 2010)
Real residential investment in Germany is found to be cointegrated with population, real national income per capita and real house prices. This evidence is consistent with a model where the trend in housing demand is determined by demographic factors and economic well-being to which supply adjusts so slowly that real house prices are affected persistently. Reunification seems to have induced two structural changes in the empirical housing market model. First, the speed of equilibrium adjustment via residential investment slowed down substantially and real house prices lost the capacity to contribute to the adjustment process. Second, the degree of persistence in the error correction term increased a lot. The changing features are key to explain significant differences in alternative trend-cycle decompositions of residential investment.
Keywords: E22; C32; 330; Residential investment; vector autoregression; trend-cycle decomposition; Germany; Wohnungsbauinvestition; Baukonjunktur; VAR-Modell; Dekompositionsverfahren; Schätzung; Deutschland